Efeito do análogo capsiate (Capsicum annuum) sobre a termogênese e perfil lipídico de ratas Wistar obesas e não obesas - Nogueira, Luciane de Souza Romero (2013)
The aim of the study was to evaluate the effect of analogous capsiate (Capsicum annuum) on thermogenesis and lipid profile of Wistar obese and non-obese. We used 64 Wistar rats, 60 days old and weighing 200g. The animals were divided into four groups (n = 16), where they received treatment for six weeks: control group (C) fed a commercial (Labina ®) and filtered water (placebo), Group Control + Capsiate (CC) : fed a commercial (Labina ®) and capsiate; Obese Group (The): fed with high fat diet and filtered water (placebo); capsiate group O + (OC): fed with high fat diet and capsiate. For evaluation of thermogenesis were measured every seven days during the experiment, rectal body temperature and weight of the rats. At 7 weeks the animals were anesthetized and euthanasia performed by exsanguination by cardiac puncture for lipid profile determination through the measurement of triglycerides, total cholesterol and HDL-Col (high density lipoprotein). The results showed an increase in temperature of the OC group, as well as increased levels of HDL-Chol in the supplemented groups (OC and CC). It is concluded that supplementation with capsiate briefly increased thermogenesis by speeding up metabolism and positively influencing the levels of HDL-Chol and can be used as another form of treatment of obesity. Further studies are needed to evaluate the potentiation of the effect of capsiate associated with regular physical activity and a balanced diet.